Customer experience in shared economy: Recommendations for companies - Jan Machala (Trends Economics and Management, 2020)
Purpose of the article: This article aims to identify the perception of customers in the shared economy, specifically their customer experience with Uber, Bolt and Airbnb, and then evaluate what these companies stand out for or what their deficiencies are, and formulate recommendations for them. Methodology/methods: The secondary research from an article in Web of Science and primary research conducted through an online questionnaire. Scientific aim: Find out customers' views on shared economy services. Findings: Shared economy services are rated very positively, however, there is still a possibility for the development of new services. Conclusions: Customers are satisfied with the services of the shared economy and feel that these services save them time and money and make it easier to solve their problem. They are also willing to recommend these services. However, they are not very loyal to a particular brand. Businesses should focus on building a positive relationship with the brand to build more loyal customers. Companies could also do this by building a community in which their custodians feel good and proud to be part of that community. The limitations of this research are mainly in the narrow focus on three companies in the field of shared economy and also the age of respondents, as the majority of respondents were in the range of 18-34 years.
Keywords: M31; 650; customer experience; shared economy; customer loyalty; recommendation; Uber; Bolt; Airbnb